A23 PHYSICIAN FACTORS ASSOCIATED WITH ADENOMA DETECTION AT COLONOSCOPY. (15th March 2019) - Pi, S; Gondara, L; Enns, R A; Gentile, L; Telford, J J
Abstract: Background: A physician's adenoma detection rate (ADR) is inversely associated with post-colonoscopy colorectal cancer (CRC) incidence and mortality. In BC, the Colon Screening Program (BCCSP) was implemented in Nov. 2013, with the goal of standardizing CRC screening. Colonoscopy quality assurance initiatives within the BCCSP include monitoring physicians' ADR, completion rates, complications as well as Direct Observation of Procedural Skills (DOPS), a validated formative assessment of colonoscopy skills. Aims: To evaluate whether physician characteristics are associated with the discovery of an adenoma in patients undergoing colonoscopy to investigate a positive fecal immunochemistry test (FIT). Methods: Data is collected prospectively from all participants in the BCCSP including age, gender, FIT value, physician performing the colonoscopy, colonoscopy findings and pathology. Physician variables are publically available through the BC College of Physicians and Surgeons'. All colonoscopies performed for a positive FIT through the BCCSP between 11/13-12/17 were included. The total number of colonoscopies performed by each physician was not available, only those performed in the BCCSP. A mixed effects logistics regression was used for data analysis. Results: 87, 542 colonoscopies performed by 263 physicians on patients between the ages of 50–74 years were included. Of the physicians, 76% were men. 65% were surgeons, 31% were gastroenterologists (GI), 3% internal medicine, and 1% family physicians. 71% had completed DOPS. The majority (39%) graduated after 2000 and 86% graduated from North American (NA) medical schools. The median annual volume of BCCSP colonoscopies per physician was 72 (10th, 90th percentile: 3, 173). Conclusions: Sub-specialty training in gastroenterology, a higher volume of colonoscopies within the program and more recent traininig were significantly associated with the detection of an adenoma at colonoscopy on multivariable regression analysis while controlling for patient age, gender and FIT value. Funding Agencies: None